Thermodynamic classification of vapor and liquid dominated reservoir and fluid geochemical parameter calculations - Mahendra P. Verma (Geofísica Internacional, 1997)
A thermodynamic definition is presented to classify vapor and liquid-dominated geothermal reservoirs. The vapor-dom¬inated reservoir has a specific volume of fluid (i.e. combined vapor and liquid) greater than the critical volume of water, whereas the liquid-dominated reservoir has a lower specific volume. A vapor-dominated reservoir is not necessarily a super¬heated steam reservoir; it can have both vapor and liquid. The PVT characteristics of geothermal fluid are considered as of pure water.A two-phase flow approach is developed to calculate fluid thermodynamic parameters; chemical speciation, pressure and temperature in a geothermal reservoir from the parameters measured in the geothermal fluid (vapor and liquid) at the well¬head separator. Steady-state flow and no heat loss or gain due to thermal conduction in the geothermal well are assumed. Conservation of mass and of total (mechanical and thermal) energy is introduced. The frictional pressure drop in the well is neglected with respect to gravitational and accelerational pressure drops. An application to well M-19A at Cerro Prieto shows that the Cerro Prieto is a two-phase vapor-dominated reservoir.